2022
DOI: 10.3390/sports10090126
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Bout Effect of Two Resistance Training Bouts on Bowling-Specific Performance in Male Cricketers

Abstract: To examine the repeated bout effect (RBE) following two identical resistance bouts and its effect on bowling-specific performance in male cricketers. Male cricket pace bowlers (N = 10), who had not undertaken resistance exercises in the past six months, were invited to complete a familiarisation and resistance maximum testing, before participating in the study protocol. The study protocol involved the collection of muscle damage markers, a battery of anaerobic (jump and sprint), and a bowling-specific performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 33 publications
0
5
3
Order By: Relevance
“…Interestingly, there were no differences in DJ in the current study, neither between bouts nor across time points within bouts. These results conflict with a recent study (Harrison et al 2022 ) reporting impaired DJ performance 24 h after the initial resistance training bout consisting of similar exercises to the current study (i.e. various lower extremity resistance exercises).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Interestingly, there were no differences in DJ in the current study, neither between bouts nor across time points within bouts. These results conflict with a recent study (Harrison et al 2022 ) reporting impaired DJ performance 24 h after the initial resistance training bout consisting of similar exercises to the current study (i.e. various lower extremity resistance exercises).…”
Section: Discussioncontrasting
confidence: 99%
“…The DJ protocol requires reactive strength attributes by optimising stretch–shortening cycle mechanics, when compared to CMJ and SJ (Ref). As such, the discrepancy in findings between the study by Harrison et al ( 2022 ) and the current study may be due to distinct training backgrounds of the participants. In the study by Harrison et al ( 2022 ), the participants were fast bowlers in cricket, that predominantly necessitates anaerobic power by optimising stretch–shortening cycle mechanics (Ramachandran et al 2021 ).…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Incorporating ‘multi-articular’ activities as both EIMD protocols and motor performance measures in EIMD research would improve the application of findings to real-world practice in sports. Multi-articular exercises commonly practiced by athletes known to cause EIMD include resistance (squats, bench press, latpull down) [ 16 - 19 ], and plyometric exercises (various jump protocols, explosvie push-ups) [ 20 - 24 ]. To date, several studies [ 18 , 20 , 22 25 ] have reported impairment in both sprint and COD performance for several days post-exercise with a concomitant increase in CK and DOMS.…”
Section: Introductionmentioning
confidence: 99%